PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Rina Mudjiyanti & Salis Saevy Maulani (Universitas Slamet Riyadi, 2017)
The study aims to examine the effect of liquidity and profitability towards thedisclosure of corporate social responsibility (CSR). The Independent variable used inthis research were liquidity and profitability, while the dependent variable wascorporate social responsibility (CSR). Population in this study were manufacturercompanies in the consumption goods sector listed in the Indonesian Stock Exchangefor the period 2013-2015. The samples in this study were selected by using purposivesampling method and obtained as many 67 observation samples. The analysistechnique used in this research was multiple linear regression analysis. The result ofthe analysis proved that the liquidity variable has negatively affect the corporatesocial responsibility with a significance value of 0,024. Variable profitability haspositive affect the corporate social responsibility with a significance value of 0,005.Keywords : corporate social responsibility, liquidity, profitability